HUBUNGAN ISLAM DAN NEGARA: Merespons Wacana Politik Islam Kontemporer di Indonesia - Hasan, Hamsah (Al-Ahkam, 2015)
This article aims to discuss the issues of the relationship between Islam and state in the Islamic political perspective in Indonesia. This study was motivated by the desire to criticize the development and â€œup and downâ€ relationship between Islam and state that is very dynamic coloring political situation in â€œIslamic majority countryâ€ Indonesia. This article concluded that understanding the relationship between religion and state with Islamic political approach is not meant to establish a religious state or an Islamic state of Indonesia, but more on filling spaces are functionally religion in order society, nation and state. The relationship between Islam and state can be integrated in a functional relationship equally aspire to nobility. Even integralistic, symbiotic, and secularistic relations, each should be viewed as a form of complementary. Facing the development of modernization, the relationship between Islam and state should be articulated as an effort to always adapt to the development of society in its various aspects, such as: the globalization of the world political economy, science and technology, the development issues of democracy, gender, human rights, pluralism, both nationally and internationally.